The Effect of Organizational Citizenship Behavior on Turnover Intention in Millenial Generation Employees - Irma Yuni Saputri; Fatiya Halum Husna (Jurnal Psikologi Teori dan Terapan, 2022)
Abstract: The phenomenon of intention turnover (the desire to move) in employees is something that cannot be avoided from an organization, the existence of intentions turnover in employees results in the employee's decision to leave the workplace. This phenomenon of turnover occurs a lot in employees, especially in the millennial generation. This study aims to determine the effect of organizational citizenship behavior on intentions turnover in the millennial generation. This research was conducted at the JNE Blitar Branch Office. The sample in this study were employees who worked at the JNE Blitar Branch Office with a total of 85 people. To collect data, two questionnaires were used, namely the organizational citizenship behavior questionnaire and the intention questionnaire turnover which had been tested for validity and reliability. This research is a quantitative research with correlation method. For statistical analysis techniques using simple linear regression with the help of SPSS V.22. The results of this study indicate that there is an insignificant effect of the organizational citizenship behavior (X) variable on the intention variable turnover (Y) with a significance value of 0.006 and an effective contribution value of 8.8%. These results can be used as a reference for further research on organizational citizenship behavior (OCB) andintentions, turnover especially in the millennial generation. Abstrak: Fenomena intensi turnover (keinginan berpindah) pada karyawan merupakan hal yang tidak dapat dihindari dari suatu organisasi, adanya intensi turnover pada karyawan berakibat pada keputusan karyawan untuk meninggalkan tempat kerjanya. Fenomena turnover ini banyak terjadi pada karyawan, khususnya pada generasi milenial. Penelitian ini memiliki tujuan untuk mengetahui pengaruh organizational citizenship behavior terhadap intensi turnover pada generasi milenial. Penelitian ini dilakukan di Kantor JNE Cabang Blitar. Sampel pada penelitian ini adalah karyawan yang bekerja di Kantor JNE Cabang Blitar dengan jumlah 85 orang. Untuk pengambilan data menggunakan dua buah angket yakni angket organizational citizenship behavior dan angket intensi turnover yang telah uji validitas dan reliabilitasnya. Penelitian ini merupakan penelitian kuantitatif dengan metode korelasi. Untuk teknik analisis statistiknya menggunakan regresi linier sederhana dengan bantuan SPSS V.22. Hasil penelitian ini menunjukkan terdapat pengaruh yang tidak signifikan dari variabel organizational citizenship behavior (X) terhadap variabel intensi turnover (Y) dengan nilai signifikasi sebesar 0,006 dan nilai sumbangan efektif sebesar 8,8% . Hasil ini dapat digunakan sebagai rujukan untuk penelitian selanjutnya mengenai organizational citizenship behavior (OCB) dan intensi turnover khususnya pada generasi milenial.